Tree species richness and composition in a fragmented landscape of the Brazilian lowland Atlantic Forest - Pessoa,Solange de Vasconcellos Albuquerque (2020)
Abstract Tropical forests are one of the most important ecosystems and loss of biological diversity in these is a major concern. We studied seven forest remnants on the coast of Rio de Janeiro, southeastern Brazil, three medium-sized (24-63 ha) and four small (5-11 ha), to assess the influence of size, degree of disturbance and isolation on composition and diversity of the tree layer. A total of 443 species in 60 families and 185 genera were recorded, with Myrtaceae, Lauraceae and Fabaceae being the most species-rich families. The results showed areas of high α-diversity (α= 34.86-75.69) and a slightly greater decline of similarity with distance between the study areas. Remnant size not explained the variation in the species composition and we found correlation between the level of disturbance and the floristic composition. The remnants had low floristic similarity, strongly influenced by the degree of disturbance. Results suggest that disturbance influences composition and diversity and confirm the importance of including both medium-sized and small remnants in the conservation of tropical forest diversity.